Mass media crisis management strategy and reputational impact in the era of global digital disruption - Suhendra, Suhendra; Ivana, Ivana; Mahdiana, Yana (Priviet Social Sciences Journal, 2025)
The rapid evolution of digital technology has significantly reshaped the way mass media communicate and manage crises, especially when unexpected situations arise and spread quickly. Digital disruption has not only accelerated the flow of information, but also increased the risk of reputational damage for media organizations. This study explores crisis management strategies adopted by several national media outlets in response to incidents involving misinformation, public backlash on social media, and breaches of journalistic ethics. Using a qualitative case study approach, this research examines how these media institutions address challenges and their impact on public trust and institutional reputation. The findings indicate that media organizations equipped with adaptive and technology-integrated crisis protocols are more capable of minimizing reputational harm. This underscores the need for media companies to modernize their crisis response systems, invest in crisis communication training for journalists, and embed digital tools into their corporate communication strategies. Beyond its practical implications, this study contributes to the broader field of strategic communication in an era marked by digital complexity and global interconnectedness.